A meta-analysis study of the association between EGFR rs2252586 mutation and the risk of glioma - Xin, Ye; Han, Fu-Gang; Chen, Dong; Chen, Jing; Fang, Chun-Xia; Lou, Li; Liu, Han (Cellular and Molecular Biology, 2017)
Several studies reported the association between Epidermal growth factor receptor (EGFR) rs2252586 mutation and glioma susceptibility. However, the results of these studies were inconsistent. A computer-based search using EMBASE and PubMed databases was conducted. Odds ratios (OR) and 95% confidence interval (CI) were used to assess the strength of association between EGFR rs2252586 mutation and glioma susceptibility. The EGFR rs2252586 mutation was significantly associated with an increased risk of glioma (OR=1.16; 95%CI, 1.11–1.21; P<0.00001). When stratified by tumor subtype, the significantly elevated risk was observed in glioblastoma (OR=1.15; 95%CI, 1.04–1.26; P=0.007) but not in oligodendroglioma (OR=1.19; 95%CI, 0.97–1.46; P=0.10). When we excluded the studies with small sample size (case number < 1000), a significant association between EGFR rs2252586 mutation and glioma susceptibility remained (OR=1.16; 95%CI, 1.09–1.22; P<0.00001). In conclusion, this meta-analysis found that EGFR rs2252586 mutation was significantly associated with glioma risk.